Ferritin Levels in Patients of Beta Thalassaemia Major - Ikram, Nadeem; Hassan, Khalid; Younas, Muhammad; Amanat, Samina (International Journal of Pathology, 2018)
In Beta Thalassaemia Major repeated blood transfusions, ineffective erythropoiesis and increased gastrointestinal ironabsorption lead to iron overload in the body. The management of the iron overload in these patients requires theadministration of iron chelators continuously and evaluation of serum ferritin levels at regular intervals. In the present studyserum ferritin levels, of the patients with beta thalassaemia major registered at two different centers of Rawalpindi andIslamabad, were measured. Majority of the patients revealed very high ferritin levels, with a mean of 3390 ng/ml. 21.34%patients had serum ferritin between 1000 to 2500 ng/ml, while 76% patients had values above 2500 ng/ml. These levelsreflect inadequate chelation and vulnerability to develop iron overload related complications. There is a dire need torationalize the chelation therapy, as at present no chelation, inadequate chelation, improper methods of chelatorsadministration, non availability of infusion pumps, non affordability of patients to purchase pumps and chelators,inappropriate evaluation of iron overload and high levels of serum ferritin gives an overall bleak view.